Discs large in the Drosophila testis: an old player on a new task - Papagiannouli, Fani; Mechler, Bernard (Fly, 2010)
Gamete development requires a coordinated soma-germ line interaction that ensures renewal and differentiation of germline and somatic stem cells. The physical contact between the germline and somatic cell populations is crucial because it allows the exchange of diffusible signals among them. The tumor suppressor gene discs large (dlg) encodes a septate junction protein with functions in epithelial cell polarity, asymmetric neuroblast division, and formation of neuromuscular junctions. Our recent work reveals a new role of dlg in the Drosophila testis, as mutations in dlg lead to testis defects and cell death. Dlg is required throughout spermatogenesis in the somatic lineage and its localization changes from a uniform distribution along the plasma membrane of somatic cells in the testis apex, to a restricted localization on the distally located somatic cell in growing cysts. The extensive defects in dlg testis underline the importance of the somatic cells in the establishment and maintenance of the male stem cell niche and somatic cell differentiation. Here, we discuss our latest findings on the role of dlg in the Drosophila testis, supporting the view that junction proteins are dynamic structures, which can provide guiding cues to recruit scaffold proteins or other signaling molecules.